Submandibular Gland Biopsy for the Diagnosis of Parkinson Disease - Beach, Thomas G.; Adler, Charles H.; Dugger, Brittany N.; Serrano, Geidy; Hidalgo, Jose; Henry-Watson, Jonette; Shill, Holly A.; Sue, Lucia I.; Sabbagh, Marwan N.; Akiyama, Haruhiko (Journal of neuropathology and experimental neurology, 2013)
ABSTRACTThe clinical diagnosis of Parkinson disease (PD) is incorrect in 30% or more of subjects particularly at the time of symptom onset. Because Lewy-type α-synucleinopathy is present in the submandibular glands of PD patients, we assessed the feasibility of submandibular gland biopsy for diagnosing PD. We performed immunohistochemical staining for Lewy-type α-synucleinopathy in sections of large segments (simulating open biopsy) and needle cores of submandibular glands from 128 autopsied and neuropathologically classified subjects, including 28 PD, 5 incidental Lewy body disease, 5 progressive supranuclear palsy (3 with concurrent PD), 3 corticobasal degeneration, 2 multiple system atrophy, 22 Alzheimer disease with Lewy bodies, 16 Alzheimer disease without Lewy bodies, and 50 normal elderly. Immunoreactive nerve fibers were present in large submandibular gland sections of all 28 PD subjects (including 3 that also had progressive supranuclear palsy); 3 Alzheimer disease with Lewy bodies subjects were also positive, but none of the other subjects were positive. Cores from frozen submandibular glands taken with 18-gauge needles (total length, 15–38 mm; between 10 and 118 sections per subject examined) were positive for Lewy-type α-synucleinopathy in 17 of 19 PD patients. These results suggest that biopsy of the submandibular gland may be a feasible means of improving PD clinical diagnostic accuracy. This would be particularly advantageous for subject selection in early-stage clinical trials for invasive therapies or for verifying other biomarker studies.